Efektivitas Media Ballcard (Balon Imunisasi dan Kartu Point) dalam Meningkatkan Persepsi Ibu Tentang Pemberian Imunisasi Pada Anak di Kel. Padang Sarai Kec. Koto Tangah - Vii Ptrh; Viona Putri Handayani; Erick Zicof; Sumihardi Sumihardi; Rapitos Sidiq; John Amos John Amos (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
The Anak Air Health Center is one of the areas with the lowest immunization coverage, recorded at 48.7% in 2022. Although there was a slight increase to 51.2% in 2024, immunization coverage in Padang Sarai Subdistrict remains relatively low. One of the main contributing factors is the poor perception of mothers regarding childhood immunization. This study aims to determine the effectiveness of Ballcard media (Immunization Balloon and Point Card) in improving mothers' perception of child immunization in Padang Sarai Subdistrict, Koto Tangah District. This study used a mixed-methods approach was used in this study. The qualitative component involved an exploratory case study supported by interview guidelines, while the quantitative component used a quasi-experimental design with a pre-test and post-test questionnaire. The study involved 25 participants and was conducted from March 27 to May 30, 2025, Kenanga 3 community health post. The findings showed that the Ballcard media successfully improved mothers' perception scores regarding childhood immunization. The median perception score increased from 57.00 before the intervention to 69.00 after the intervention. The Immunization Balloon and Point Card media proved to be an effective, engaging, and easy-to-understand educational tool, especially in enhancing mothers’ perception of immunization in the working area of the Anak Air health center. Keyowrds : Immunization, Mother of Toddle, Immunization Ballon, Point Card